Climate change and water resources in the Himalayas - Joëlle Smadja; Olivia Aubriot; Ornella Puschiasis; Thierry Duplan; Juliette Grimaldi; Mickaël Hugonnet; Pauline Buchheit (Revue de Géographie Alpine)
In the Himalayas, where the increase in temperatures is higher than the world average, climate change is expected to impact water resources in a particularly significant manner. Whereas climate specialists using measurements and simulations play down this statement by underlining uncertainties and differences between the west and east of the range, the media and development agencies tend to paint a uniform picture of a water shortage now and in the future. As part of an interdisciplinary programme (glaciology, hydrology, agronomy, geography) in the Koshi basin in Nepal, we discuss these remarks, while stressing the need to distinguish between situations according to the geographical units and to take into account the cultural, social and economic context when addressing this subject. The investigations that we carried out at four fieldwork sites, which are representative of Nepalese milieus, aimed to find out whether populations noticed any variations in water resources that affected their practices (farming, livestock breeding, tourism) and if they attributed them to climate change. Our results show contrasting situations and changes in practices with no obvious connection to the climate. Among other things, they provide information about snow, a parameter that has been measured incorrectly and underestimated in simulations, and they show that populations are more affected by fluctuations in rainfall patterns than by the melting of glaciers and the snow cover. Lastly, they highlight the geographical units and population groups most likely to be affected by climatic variations.